1998
DOI: 10.1159/000007533
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis: Present and Future

Abstract: Cystic fibrosis (CF) is an inherited disorder of epithelial chloride transport affecting primarily pancreas, lungs, gut, liver and exocrine glands. The defect is caused by defects of the cystic fibrosis transmembrane regulation gene on chromosome 7. Genotyping has proved useful in identifying gene carriers, a definitive diagnosis, and in antenatal diagnosis. Genotype/phenotype relationships have shown that the commonest cause of pancreatic insufficiency is the D F508 mutation. Clinical trials are exploring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…In cystic fibrosis that is not caused by the common D F508 mutation but results from other mutations such as R117H mutation, acute pancreatitis may develop. 131 In elderly persons, the pancreas may contain ducts narrowed by ductal papillary hyperplasia, a lesion that has now been termed pancreatic intraepithelial neoplasia type 1B. 132 In association with this lesion, there may be patchy lobular fibrosis in the periphery of the pancreas (Figure 25).…”
Section: Pancreatic Fibrosis Not Associated With Symptoms Of Chronic mentioning
confidence: 99%
“…In cystic fibrosis that is not caused by the common D F508 mutation but results from other mutations such as R117H mutation, acute pancreatitis may develop. 131 In elderly persons, the pancreas may contain ducts narrowed by ductal papillary hyperplasia, a lesion that has now been termed pancreatic intraepithelial neoplasia type 1B. 132 In association with this lesion, there may be patchy lobular fibrosis in the periphery of the pancreas (Figure 25).…”
Section: Pancreatic Fibrosis Not Associated With Symptoms Of Chronic mentioning
confidence: 99%
“…Entretanto, com exceção para insuficiência pancreá-tica e a mutação delta F508, não se tem encontrado nenhuma correlação entre fenótipo e genótipo (14) . Tem-se demonstrado que alguns fatores externos podem influenciar o curso clínico da FC, entre os quais a infecção bacteriana, principalmente por Pseudomonas aeruginosa (15) , e exposição à fumaça de cigarro (16) . No nosso estudo não foi possível mostrar diferenças na função pulmonar conforme a colonização bacteriana, visto que a maioria dos pacientes (94,23%) já mostrava colonização por P. aeruginosa.…”
Section: Discussão E Conclusãounclassified
“…In subsequent studies, proton pump inhibitors (PPIs) proved their efficacy and safety. Several clinical GERD trials have already shown pantoprazole to be superior to H 2 -receptor antagonists [7, 8, 9, 10, 11, 12, 13, 14]. The proportion of patients relieved of symptoms or healed is significantly higher with PPIs.…”
Section: Introductionmentioning
confidence: 99%